Designing SOCs with configured cores : unleashing the tensilica Xtensa and diamond cores. - Leibson, Steve, ....- (Amsterdam : Elsevier, 2006)
Inhoudsopgave : 1.Introduction to 21st-century SOC design.2.The SOC design flow.3.Xtensa architectural basics.4.Basic processor configurability.5.MPSOC system architectures and design tools.6.Introduction to diamond standard series processor cores.7.The diamond standard series 108Mini processor core.8.The diamond 212GP controller core.9.The diamond 232L CPU core.10.The diamond 570T superscalar CPU core.11.The diamond 330HiFi audio DSP core.12.The diamond 545CK DSP core.13.Using fixed processor cores in SOC designs.14.Beyond fixed cores.15.The future of SOC design.
Keywords: Geïntegreerde schakelingen